Pengaruh Kualitas Layanan dan Kepercayaan terhadap Kepuasan Pengguna Shopee di Daerah Istimewa Yogyakarta - Rinaldi Rinaldi; Endah Marendah Ratnaningtyas; Rista Gonaria Naiheli (SENTRI: Jurnal Riset Ilmiah, 2026)
This study is motivated by the growing use of e-commerce in Indonesia, particularly Shopee, which has become one of the most popular online shopping platforms. Shopee offers numerous advantages such as a wide variety of payment methods, attractive promotions, and fast delivery services. However, the platform still faces challenges in service quality and complaint handling, which can negatively impact user satisfaction. Therefore, the aim of this research is to examine the influence of service quality and trust on user satisfaction among Shopee users in the Special Region of Yogyakarta. A quantitative research approach was employed using a survey method. Data were collected through questionnaires distributed to 100 respondents who are active users of the Shopee application. The sampling technique used was purposive sampling. The data were analyzed using validity and reliability tests, t-tests, F-tests, and multiple linear regression analysis to test the hypotheses. The findings indicate that both service quality and trust significantly influence user satisfaction. These variables, both partially and simultaneously, contribute positively to users’ overall satisfaction with Shopee. Service quality aspects—such as responsiveness, reliability, and ease of use—along with trust factors—such as platform credibility and transaction security—play a critical role in shaping user perceptions and satisfaction. These results highlight the importance for e-commerce platforms like Shopee to continually improve service delivery and build customer trust as key strategies to enhance user experience, encourage customer loyalty, and remain competitive in the dynamic digital marketplace.